KINERJA PORTOFOLIO SAHAM BERDASARKAN STRATEGI INVESTASI MOMENTUM PADA INDUSTRI MANUFAKTUR - Saputro, R. Narendra; Badjra, Ida Bagus (E-Jurnal Manajemen; Vol 5 No 1 (2016), 2016)
The purpose of this study was to determine the performance of a stock portfolio using momentum investment strategy in the manufacturing industry. The scope of this research area is the companies in the manufacturing industry listed in Indonesia Stock Exchange during the period January 2009 to December 2014. 120 samples of manufacturing companies were taken using purposive sampling method. Methods of data collection is done through non-participant observation and analysis techniques using paired sample t-test. Based on the results of data analysis found that the performance of winner portfolio was lower than the performance of loser portfolio in the period of the next possession, and then, there is a difference between the winner-loser portfolio performance in the formation period and the holding period. This indicates that the momentum investment strategy is not profitable when applied in the Indonesian capital market.
Keywords: performance of stock portfolio, momentum investment strategy, manufacturing industry.